The Efficacy of Mylohyoid Nerve Anesthesia in Dental Implant Placement at the Edentulous Posterior Mandibular Ridge - (:unkn) unknown (ALLEN PRESS INC, 2012)
The aim of this study is to evaluate the anesthetic efficacy of mylohyoid and buccal nerve anesthesia at the posterior edentulous mandible versus regional anesthetic block to the inferior alveolar nerve in dental implant surgery. The study was composed of 2 groups. In the first group (group A), 14 voluntary adults (7 female and 7 male) received local infiltrations of 1 mL articaine HCl 4% with epinephrine 1/200 000 to the ipsilateral mylohyoid and buccal nerves. In the second group (group B, control; 9 female and 5 male adults), the inferior alveolar and the buccal nerve blocks were performed. Visual analog scales were obtained from patients to determine the level of pain during incision, drilling, implant placement, and suturing stages of implant surgery. A combination of buccal and mylohyoid nerve block offered an acceptable level of anesthesia. Two patients from group A stopped the ongoing surgery and had extraregional anesthesia by inferior alveolar nerve block. In group B, patients were operated on successfully. Local anesthetic infiltrations of the mylohyoid and the buccal nerve may be considered alternative methods of providing a convenient anesthetic state of the posterior mandibular ridge.
Keywords: mylohyoid nerve; posterior edentulous mandible; local anesthesia; INFERIOR ALVEOLAR; LOCAL-ANESTHESIA